2005
DOI: 10.1111/j.1532-950x.2005.00036.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Cathepsin K and Tartrate‐Resistant Acid Phosphatase in Synovium and Cranial Cruciate Ligament in Dogs with Cruciate Disease

Abstract: Production of matrix-degrading enzymes by the synovium may induce progressive pathologic rupture of the CCL. Therefore, these collagenolytic pathways may offer a novel target for medical therapy of joint inflammation in canine patients with cruciate disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
67
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 39 publications
6
67
0
2
Order By: Relevance
“…Furthermore, a higher number of TRAP positive cells was seen in the synovium of the experimental group but few cells or none were seen in the control group. Histochemistry for TRAP produced results was consistent with those of an earlier study which reported an increase in the number of TRAP + cells in the synovium from humans with arthritis and dogs with osteoarthritis secondary to the naturally occurring rupture of the cranial cruciate ligament (Konttinen et al, 2001;Muir et al, 2005). These results suggest that an increase in the number of TRAP + cells in the synovium is related to the development of OA.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, a higher number of TRAP positive cells was seen in the synovium of the experimental group but few cells or none were seen in the control group. Histochemistry for TRAP produced results was consistent with those of an earlier study which reported an increase in the number of TRAP + cells in the synovium from humans with arthritis and dogs with osteoarthritis secondary to the naturally occurring rupture of the cranial cruciate ligament (Konttinen et al, 2001;Muir et al, 2005). These results suggest that an increase in the number of TRAP + cells in the synovium is related to the development of OA.…”
Section: Discussionsupporting
confidence: 82%
“…Recent reports have shown that the synovial intima of OA contains a large number of TRAP-containing cells (TRAP + cells) such as dendritic cells and macrophage-like cells (Muir et al, 2005). It was demonstrated that TRAP positive cells play an important role in cytokine synthesis, in the expression of MMPs and cartilage damage (Tsuboi et al, 2003;Adamopoulos et al, 2006b).…”
mentioning
confidence: 99%
“…TRAP + mononuclear cells are activated macrophages typically found in synovium of dogs with CR, but not in normal synovium [11]. In the present study, we found that a majority of synovial biopsies from both the index stifle (83%) and the contralateral stifle (67%) contained TRAP + macrophages.…”
Section: Discussionsupporting
confidence: 47%
“…The arthroscopic synovial assessment method we used was adapted from a validated scoring system used in human beings [27]. Our selection of histologic, serum, and synovial fluid markers was chosen on the basis of past work that has shown that inflamed synovium in CR stifles typically contains a mixed population of mononuclear cells, often aggregated into nodules [10],[11]. We also determined intra- and inter-observer variability to help validate our arthroscopic assessment method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation